Simvastatin therapy in cyclosporine A-induced alveolar bone loss in rats - Nassar, P. O. [UNESP]; Nassar, C. A.; Guimaraes, M. R. [UNESP]; Aquino, S. G. [UNESP]; Andia, D. C. [UNESP]; Muscara, M. N.; Spolidório, Denise Madalena Palomari [UNESP]; Rossa, C. [UNESP]; Spolidório, Luis Carlos [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Background and Objective:Cyclosporine A treatment is important in the therapy of a number of medical conditions; however, alveolar bone loss is an important negative side-effect of this drug. As such, we evaluated whether concomitant administration of simvastatin would minimize cyclosporine A-associated alveolar bone loss in rats subjected, or not, to experimental periodontal disease.Material and Methods:Groups of 10 rats each were treated with cyclosporine A (10 mg/kg/day), simvastatin (20 mg/kg/day), cyclosporine A and simvastatin concurrently (cyclosporine A/simvastatin) or vehicle for 30 days. Four other groups of 10 rats each received a cotton ligature around the lower first molar and were treated similarly with cyclosporine A, simvastatin, cyclosporine A/simvastatin or vehicle. Calcium (Ca(2+)), phosphorus and alkaline phosphatase levels were evaluated in serum. Expression levels of interleukin-1 beta, prostaglandin E(2) and inducible nitric oxide synthase were evaluated in the gingivomucosal tissues. Bone volume and numbers of osteoblasts and osteoclasts were also analyzed.Results:Treatment with cyclosporine A in rats, with or without ligature, was associated with bone loss, represented by a lower bone volume and an increase in the number of osteoclasts. Treatment with cyclosporine A was associated with bone resorption, whereas simvastatin treatment improved cyclosporine A-associated alveolar bone loss in all parameters studied. In addition, simvastatin, in the presence of inflammation, can act as an anti-inflammatory agent.Conclusion:This study shows that simvastatin therapy leads to a reversal of the cyclosporine A-induced bone loss, which may be mediated by downregulation of interleukin-1 beta and prostaglandin E(2) production.
Keywords: simvastatin; cyclosporine A; alveolar bone loss; periodontitis